A colorimetric quinoline-based chemosensor for sequential detection of copper ion and cyanide anions. Issue 38 (21st September 2017) - Wu, Chenjun; Wang, Jianbo; Shen, Jinjin; Zhang, Chenyu; Wu, Zuoyi; Zhou, Hongwei
Abstract: A new quinoline-based chemosensor (CQ ) for sequential detection of Cu 2+ and CN − has been synthesized, where diaminomaleonitrile is introduced as recognition group. After addition of Cu 2+, sensorCQ in aqueous solution (DMSO/H2 O) displays remarkable colorimetric change from the light yellow to red, which is attributed to the extended intermolecular charge transfer inCQ -Cu 2+ complex. SensorCQ shows a highly selective and sensitive response to Cu 2+, which can be used as Test strips to conveniently monitor Cu 2+ . In addition, CQ -Cu 2+ complex could be applied to monitor sequentially cyanide anion with dramatic colour change based on copper ion complex displacement mechanism. Graphical abstract: Highlights: We report a new quinoline-based colorimetric chemosensorCQ for Cu 2+ with high selectivity and sensitivity. Test strips immersed sensorCQ can be used to conveniently monitor Cu 2+ by naked-eyes. SensorCQ treated with Cu 2+ can be applied to sequentialy detect cyanide anion.